DECENTRALIZATION OF NATIONAL ECONOMY MANAGEMENT: THE EXPERIENCE OF EUROPEAN COUNTRIES - Galtsova, O. L. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The purpose of the article is to summarize the experience of foreign countries in the implementation of the decentralization reform and identify the main problems that arise in Ukraine. The experience of the European countries on decentralization of management was shown in the article. It has been established that in recent years decentralization has become a global phenomenon. The process of decentralization in different countries, namely in France, Poland, Germany, Spain, Sweden and the United Kingdom, was analyzed, and the advantages and disadvantages of its implementation were indentified. The process of powers redistribution between regional, central, local levels of government was established as the main advantage. Local authorities can resolve any issues related to the life provision of the population in their territory. The possibility of introducing other decentralization models without increasing the local level by the current practice of the EU member was determined. In particular, Spain is an example of so-called regional decentralization, when the main results of decentralization are concentrated in the direction of transferring powers from the central government to the governments of the autonomies (regions). The experience of Britain, Germany, as well as France and the Scandinavian countries allows us to see how different the background, content and results of decentralization are. For the Swedish model of local self-government, unlike the British and French, significant aspects of functionality and participation. Political space is determined not only by the state, but also by the low level of decision-making, such as provinces and municipalities. The experience of public administration reform in European countries has shown that the limits of decentralization are due to the specifics of the center-local relations and the potential of local self-government. Political decentralization and commercialization of public services in England, increasing the role of the communes and the gradual transition to market relations in Germany, administrative reforms and the activation of local communities in France - all these processes reflect one or another model of decentralization, which are guided by other European countries, particular in Ukraine.